2014
DOI: 10.1155/2014/567257
|View full text |Cite
|
Sign up to set email alerts
|

CFD Analysis to Study Effect of Circular Vortex Generator Placed in Inlet Section to Investigate Heat Transfer Aspects of Solar Air Heater

Abstract: CFD analysis of 2-dimensional artificially roughened solar air heater duct with additional circular vortex generator, inserted in inlet section is carried out. Circular transverse ribs on the absorber plate are placed as usual. The analysis is done to investigate the effect of inserting additional vortex generator on the heat transfer and flow friction characteristics inside the solar air heater duct. This investigation covers relative roughness pitch in the range of 10 ≤ P/e ≤ 25 and relevant Reynolds numbers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 15 publications
0
11
0
1
Order By: Relevance
“…The values of Reynolds number, Nusselt number, average Nusselt number, friction factor and thermal-hydraulic performance have been calculated using the following equations [15,17,[19][20][21][22][23]:…”
Section: Data Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The values of Reynolds number, Nusselt number, average Nusselt number, friction factor and thermal-hydraulic performance have been calculated using the following equations [15,17,[19][20][21][22][23]:…”
Section: Data Reductionmentioning
confidence: 99%
“…However, only a few investigations are available those are based on CFD approaches [23][24][25][26][27][28][29][30][31][32][33][34]. Gawande et al [23] conducted a numerical study on the effect of the transverse circular vortex type generator in an air channel. It was observed that the performance of the transverse circular vortex type generator in the channel was better than that of the smooth wall channel.…”
mentioning
confidence: 99%
“…This is a simplified version of the vortex system generated close to the wing tips, but the reader is reminded that the Augmented Betz method is also capable of producing more complex, multivortex systems. The methodology of generating this system is similar to “effect‐based” models used in Gawande, Dhoble, and Zodpe [], Waithe [], and Lane []. More complex immersed boundary‐based solvers may be used in the future.…”
Section: Resultsmentioning
confidence: 99%
“…To achieve higher accuracy, the convergence criteria between two consecutive iterations is set to be relative deviation less than 10 -6 for energy equation and less than 10 -3 for solution in velocity and the continuity equation. The above discussed method of investigation has been validated in the author's previous work [44].…”
Section: Solution Methodsmentioning
confidence: 99%